PERAN SELF CONTROL DALAM MEMODERASI PENGARUH HEDONIC MOTIVES DAN SHOPPING LIFESTYLE TERHADAP IMPULSE BUYING - Yordan Hermawan Apidana; Kholifah Kholifah (LP3M Universitas Putra Bangsa, 2022)
For career women, appearance is an important thing that must be considered and this can trigger a lifestyle shopping culture and hedonism that leads to high impulsive behavior. Career women who have families are considered to have high self-control against impulsive behavior towards online shopping, namely because the need for family is a priority compared to their own needs. The purpose of this study was to determine the effect of hedonic motives, shopping lifestyle on impulse buying which is moderated by self-control. This research is a quantitative research and the respondents in this research are 244. In this study the sample was taken by non-probability sampling, namely by purposive sampling technique. Based on data analysis, it is known that: (1) hedonic motives have a positive and significant effect on impulse buying, (2) shopping lifestyle has a positive and significant effect on impulse buying, (3) hedonic motives do not moderate the effect of shopping lifestyle on impulse buying, (4 ) self-control moderates the effect of shopping lifestyle on impulse buying.